2019
DOI: 10.5194/acp-2019-657
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vertical profiles of sub-micron aerosol single scattering albedo over Indian region immediately before monsoon onset and during its development: Research from the SWAAMI field campaign

Abstract: <p><strong>Abstract.</strong> Vertical structures of aerosol single scattering albedo (SSA), from near the surface through the free troposphere, have been estimated for the first time at distinct geographical locations over the Indian mainland and adjoining oceans, using in-situ measurements of aerosol scattering and absorption coefficients aboard the FAAM BAe-146 aircraft during the South West Asian Aerosol Monsoon Interactions (SWAAMI) campaign from June to July 2016… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…However, there are few exceptions. SSA values over the Bay of Bengal during SWAAMI campaign were reported as 0.84 + 0.07 during June-July by Manoj et al (2019), whereas CERES-MODIS retrieves a higher SSA of ~0.89 for the same time period. This large variation could be due to frequent cloud cover during the monsoon season, leading to fewer SSA points retrieved over the ocean and land.…”
Section: Validationmentioning
confidence: 99%
“…However, there are few exceptions. SSA values over the Bay of Bengal during SWAAMI campaign were reported as 0.84 + 0.07 during June-July by Manoj et al (2019), whereas CERES-MODIS retrieves a higher SSA of ~0.89 for the same time period. This large variation could be due to frequent cloud cover during the monsoon season, leading to fewer SSA points retrieved over the ocean and land.…”
Section: Validationmentioning
confidence: 99%
“…Why elevated aerosols are not seen over mainland? In fact several earlier studies have reported elevated aerosol layers over mainland (Mishra et al, 2010;Ganguly et al,2006;Niranjan et al, 2007;Sinha et al, 2013;Venkat Ratnam et al, 2018). Further, it is mentioned that highest values are observed within 3 km from the surface.…”
mentioning
confidence: 89%
“…The uncertainty due to the combined effect of AOD, SSA and asymmetry parameter on the top of the atmosphere forcing was found to be ∼ 1.8 W/m2. Estimation of uncertainty has been discussed in detail in many papers from the group (Moorthy et al, 2009, Satheesh et al, 2010 and hence not repeated here. We also found that the uncertainty in the instantaneous atmospheric forcing for the cases shown in figure 9 was ∼4.2 W/m2.…”
mentioning
confidence: 99%